2007
DOI: 10.1016/j.jet.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of costless pre-play communication: Experimental evidence from games with Pareto-ranked equilibria

Abstract: Cheap talk is shown to facilitate coordination on the unique efficient equilibrium in experimental order-statistic games. This result is roughly consistent with theoretical predictions according to which cheap talk promotes efficient Nash play. The evidence concerning the mechanisms that theory appeals to is mixed: Frequent agreement of messages and actions is consistent with messages being viewed as self-committing. Risk in the underlying game and the absence of self-signaling messages may explain why message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
167
7
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 278 publications
(194 citation statements)
references
References 29 publications
19
167
7
1
Order By: Relevance
“…Unlike most of the literature (e.g., Blume and Ortmann 2007;Cartwright et al 2013;Sahin et al 2015, in different environments), we found that in this challenging setting the mechanisms failed to overcome coordination failure and had only limited effectiveness in preventing it. The mechanisms had some effect in the short run as some players attempted to choose a higher effort but in the long run most players fell back to the lowest possible effort.…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…Unlike most of the literature (e.g., Blume and Ortmann 2007;Cartwright et al 2013;Sahin et al 2015, in different environments), we found that in this challenging setting the mechanisms failed to overcome coordination failure and had only limited effectiveness in preventing it. The mechanisms had some effect in the short run as some players attempted to choose a higher effort but in the long run most players fell back to the lowest possible effort.…”
Section: Resultscontrasting
confidence: 97%
“…3 Coordination failure in a minimum effort game could be prevented if the game is modified from the beginning, possibly avoiding the decline of effort choices to a low level. For example, Blume and Ortmann (2007) find that pre-play communication significantly increases efficiency relative to the baseline treatment with no communication. 4 Cartwright et al (2013) let one of the players "lead-by-example" by choosing effort before the other players.…”
Section: Introductionmentioning
confidence: 95%
“…The outcome was essentially the same even after payoff efficient precedents emerged in a treatment (B) that was inserted between treatments A and A' for four out of six sessions. Several other experimenters -in baseline treatments for various modifications reported in those papers --replicated this unraveling result with the same payoff matrix, and with subject numbers varying from 6 -14 (e.g., Cachon and Camerer, 1996;Bornstein, Gneezy and Nagel, 2002;Blume and Ortmann, 2005;Chaudhuri, Schotter and Sopher, 2005). Other experimenters -also in baseline treatments for various modifications reported in those papers --chose structurally similar payoff matrices (e.g., linear deviation costs, no negative payoffs) with slightly more or less action choices (e.g., Berninghaus and Ehrhart, 1998;Knez and Camerer, 1994;Weber, Camerer, Rottenstreich and Knez, 2001;Brandts and Cooper, 2004, 2005a and also replicated this result.…”
Section: Laboratory Evidence Of Coordination Failures and Successesmentioning
confidence: 58%
“…Furthermore, the initial median constituted a strong precedent from which subjects had trouble extracting themselves. Blume and Ortmann (2005), in their baseline treatments, replicated this result by using the same payoff matrix, the same number of subjects, and the same feedback conditions. So did Cachon and Camerer (1996).…”
Section: Laboratory Evidence Of Coordination Failures and Successesmentioning
confidence: 64%
See 1 more Smart Citation